(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the age of digital transformation, bioinformatics has emerged as a cornerstone of modern biological research, serving as a bridge between data science and the life sciences. The ever-increasing volume of genomic data, driven by advances in high throughput sequencing technologies, has led to the conceptualization of DNA as a form of digital code—"digital DNA"—that can be stored, analyzed, and interpreted using computational tools. This paradigm shift has opened new avenues for understanding the fundamental mechanisms of life, diagnosing diseases, and designing personalized medicaltreatments. However, the integration of massive biological datasets with complex algorithms also brings forth significant challenges. These include issues related to data storage, privacy, algorithmic bias, and the need for interdisciplinary expertise. As bioinformatics continues to evolve, its future success will depend on addressing these challenges while harnessing the full potential of digital DNA for both scientific discovery and societal benefit.